Regulating style : intellectual property law and the business of fashion in Guatemala - Thomas, Kedron, 1979- (University of California Press, 2016)
"Fashion knock-offs are everywhere. Even in the out-of-the-way markets of highland Guatemala, fake branded clothes offer a cheap, stylish alternative for people who can't afford high-priced originals. Fashion companies have taken notice, ensuring that international trade agreements include stronger intellectual property protections to prevent brand 'piracy.' Regulating Style approaches the fashion industry from the perspective of Indigenous Maya people who make and sell knock-offs, asking why they copy and wear popular brands, how they interact with legal frameworks and state institutions that criminalize their livelihood, and what is really at stake for fashion companies in the global regulation of style"--Provided by publisher.